Leitura e inteligibilidade da fala em crianças usuárias de implante coclear - Lucchesi, Fernando Del Mando (2018)
Children with prelingual hearing impairment find in the cochlear implant an important alternative for rehabilitation and social integration through listener and oral repertoires. However, during the rehabilitation process, many of these children may face difficulties learning discriminative repertories that are important for improving device usage. Despite the good development of listening skills, predicted by broadly studied variables, the scientific literature points to difficulties in producing intelligible vocal responses – that is, responses with point-to-point correspondence to verbal community conventions – and in the network of relations that describe reading and writing. Specifically concerning oral production, there is consistent data suggesting that these children present responses that are more intelligible during reading tasks than during picture naming tasks. Recent studies point to the interdependence between reading and naming responses through the conceptual and methodological foundations of the equivalence relations paradigm. This paradigm enables multiple exemplar instruction (of stimulus control and response topography) and transfer of control from printed words to pictures. The current work presents three chapters with three distinct studies on this topic: Chapter 1 brings a systematic literature review of verbal repertoire interventions on implanted persons. Most studies focus on the evaluation and prediction of cochlear implanted users’ performance. Results point to the need of greater investment in the planning and evaluation of intervention programs that target the repertoires involved in reading, writing, listening and speaking, indicating positive effects of programmed and individualized teaching. The second chapter describes a pilot study that assessed the effects of a program that teaches reading and writing using multiple picture naming probes with a single subject. This methodological refinement allowed the assessment of how the teaching program affected the quality of the child’s vocal responses as well as possible additional effects of the multiple probes, creating a context to extend the investigation to the study described in Chapter 3. This last study was characterized by exposing four hearing impaired implanted children to the teaching program with multiple figure-naming and word-reading probes between sets of stimuli and training sessions, in a multiple baseline design. This study replicates and expands previous studies by using a refined methodology that increased the quality of participants’ vocal verbal responses for naming pictures and reading words. The discussion highlights the importance of a solid foundation of knowledge on teaching and learning processes in order to obtain better performance with cochlear implants and point future directions for intervention studies.